The impact of HIV/AIDS among different organizations in Lesotho and how they respond to the challenge : a Lesotho study - Sekhibane, Veronica Mabohle (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University,2005.